Not just another DE

Calculus Level 5

x 2 d y d x + 0 x x 2 y 5 d x = 0 x^2\dfrac{dy}{dx}+\int_0^x x^2y^5\,dx=0

Let y y be a function of x x satisfying the above equation and has a maximum value of 1 1 at x = 0 x=0 .

Find 0 x 2 y 5 d x \displaystyle \int_0^\infty x^2y^5\,dx

4 \sqrt4 1 \sqrt1 5 \sqrt5 2 \sqrt2 3 \sqrt3

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Jon Haussmann
Nov 13, 2018

I found that y = 3 x 2 + 3 y = \sqrt{\frac{3}{x^2 + 3}} using a terrible brute force technique.

@Digvijay Singh , maybe you have a nice solution.

The given DE is a Lane-Emden equation for n = 5 n=5 .

You can read about it on this article

Digvijay Singh - 2 years, 7 months ago

How do you know that this is the only solution. May be we have to convert it in to systems of differential equations by introducing the variable y1=dy/dx and then use the existence uniqueness theorem.

Srikanth Tupurani - 2 years, 7 months ago

Log in to reply

You might want to read this article

Digvijay Singh - 2 years, 7 months ago

Let's first take derivative with respect to x, we get

1 x 2 d d x x 2 d d x y + y 5 = 0 \displaystyle \dfrac{1}{x^{2}}\dfrac{d}{dx}x^{2}\dfrac{d}{dx}y+y^{5}=0

Next, we substitute in y = u x 1 / 2 \displaystyle y=ux^{-1/2} (I got this substitution from considering "balance of variable" i.e. 1 x 2 d d x x 2 d d x y y 5 \displaystyle \dfrac{1}{x^{2}}\dfrac{d}{dx}x^{2}\dfrac{d}{dx}y \sim y^{5} , so, y x 1 / 2 \displaystyle y \sim x^{-1/2} and hence, the guess.)

Now, y = u x 1 / 2 1 / 2 u x 3 / 2 \displaystyle y'=u'x^{-1/2}-1/2ux^{-3/2} and y " = u " x 1 / 2 u x 3 / 2 + 3 / 4 u x 5 / 2 y"=u"x^{-1/2}-u'x^{-3/2}+3/4ux^{-5/2} and so,

1 x 2 d d x x 2 d d x y + y 5 = x 2 u " + x u 1 / 4 u + u 5 = 0 \displaystyle \dfrac{1}{x^{2}}\dfrac{d}{dx}x^{2}\dfrac{d}{dx}y+y^{5}=x^{2}u"+xu'-1/4u+u^{5}=0

x 2 u " + x u = d 2 d l n x 2 u \displaystyle x^{2}u"+xu'=\dfrac{d^{2}}{dlnx^{2}}u So, we have turned the equation into the form we are familiar with.

( d u / d l n x ) 2 = A + u 2 4 u 6 3 \displaystyle (du/dlnx)^{2}=A+\dfrac{u^{2}}{4}-\dfrac{u^{6}}{3} but d u / d l n x = x u = 0 = u du/dlnx=xu'=0=u at x=0, so, A=0

d u / d l n x = u 1 4 u 4 3 \displaystyle du/dlnx=u\sqrt{\dfrac{1}{4}-\dfrac{u^{4}}{3}}

d u u 1 4 u 4 3 = 3 2 d u 2 u 2 3 4 u 4 \displaystyle \int { \frac { du }{ u\sqrt { \frac { 1 }{ 4 } -\frac { { u }^{ 4 } }{ 3 } } } } =\frac { \sqrt { 3 } }{ 2 } \int { \frac { d{ u }^{ 2 } }{ { u }^{ 2 }\sqrt { \frac { 3 }{ 4 } -{ u }^{ 4 } } } }

u 2 = 3 2 s i n θ \displaystyle u^{2}=\dfrac{\sqrt{3}}{2}sin\theta

d θ sin θ = 1 2 ln 1 + cos θ 1 cos θ = l n A + l n x \displaystyle \int { \frac { d\theta }{ \sin { \theta } } } =\frac { -1 }{ 2 } \ln { \frac { 1+\cos { \theta } }{ 1-\cos { \theta } } } =lnA+lnx

c o s θ = A x 2 A + x 2 = 3 / 4 u 4 3 / 4 \displaystyle cos \theta=\dfrac{A-x^{2}}{A+x^{2}}=\dfrac{\sqrt{3/4-u^{4}}}{\sqrt{3/4}} so,

u 4 = 3 A x 2 ( A + x 2 ) 2 = y 4 x 2 \displaystyle u^{4}=\dfrac{3Ax^{2}}{(A+x^{2})^{2}}=y^{4}x^{2} now, y=1 at x=0 means A=3 so y = 3 3 + x 2 \displaystyle y=\sqrt{\dfrac{3}{3+x^2}} now the integral asked is plain easy, so, I will just leave it at this stage.

1 pending report

Vote up reports you agree with

×

Problem Loading...

Note Loading...

Set Loading...